Desktop based virtual reality to enhance role clarification. - Botha, B. S.; Hugo, L.; Nyoni, C. N. (Journal of Interprofessional Care)
Role clarification is essential for health care professionals to understand each role in a health professions team. However, educators struggle to design and execute effective learning activities focusing on role clarification within interprofessional education programmes, often due to a limited understanding of each other's professions or limited experience within interprofessional teams. To assist in addressing this issue, a qualitative exploratory design was applied using a desktop-based virtual reality (VR) simulation to facilitate a discussion on role clarification and explore the influence of virtual reality in the development of shared mental models about role clarification. Ten educators were recruited to participate in a workshop, after which they engaged in a discussion session on the facilitation of role clarification in Interprofessional education (IPE) programmes. Educators were first expected to individually create their desktop-based virtual reality scenario, which reflected their professional roles. Once completed, other educators interacted with their scenario by asking questions and reflecting on their practice as educators and practitioners. Narrative data collected during the discussions on the scenarios of each of the educators were analyzed thematically, resulting in four themes, namely "skills and tasks," "responsibilities in patient care," "tools of the trade" and "communication." The educators discussed various aspects of their professional roles but ignored the fact that they have dual roles as practitioners and educators. The length of the workshop limited the development of fully shared mental models. Future research should explore the longitudinal use of desktop-based VR in role clarification toward shared mental models.